2011
DOI: 10.3109/0886022x.2011.568147
|View full text |Cite
|
Sign up to set email alerts
|

The Effects ofSyzygium aromaticum-Derived Oleanolic Acid on Glycogenic Enzymes in Streptozotocin-Induced Diabetic Rats

Abstract: Studies indicate that the antihyperglycemic effects of Syzygium aromaticum-derived oleanolic acid (OA) are mediated in part through increased hepatic glycogen synthesis. Accordingly, this study assessed the influence of OA on the activity of glucokinase (GK) and hexokinase (HK) of skeletal muscle and liver tissues in streptozotocin (STZ)-induced diabetic rats. After 5 weeks of OA treatment, hepatic and gastrocnemius muscle glycogen concentrations and activities of GK and HK were measured spectrophotometrically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 34 publications
2
37
0
Order By: Relevance
“…12,25,26 The spectra of the plant derived MA elucidated using 1 H-and 13 C-NMR compared with previously reported data of maslinic acid. 28,29 Streptozotocin used to induce diabetes mellitus selectively destroys pancreatic b-cells 30 and the systemic changes which occur after its injection are related to the induced diabetic state.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…12,25,26 The spectra of the plant derived MA elucidated using 1 H-and 13 C-NMR compared with previously reported data of maslinic acid. 28,29 Streptozotocin used to induce diabetes mellitus selectively destroys pancreatic b-cells 30 and the systemic changes which occur after its injection are related to the induced diabetic state.…”
Section: Discussionmentioning
confidence: 99%
“…25 Briefly, liver and gastrocnemius muscle tissue samples (1-1.5 g) were homogenized in 2 mL of 30% potassium hydroxide solution and digested at 100 C for 30 min and then cooled in ice-saturated sodium sulphate. The glycogen was precipitated with ethanol, pelleted and resolubilized in deionized water.…”
Section: Glycogenmentioning
confidence: 99%
See 1 more Smart Citation
“…Various medicinal plant extracts have been reported to significantly reduce food intake possibly through the reduction of plasma ghrelin levels (Bast et al, 2002;Fong, 2002). Studies conducted in our laboratory have shown that Syzygium aromaticum-derived oleanolic acid (OA) and maslinic acid (MA) reduce blood glucose concentrations in STZ-induced diabetic rats in sub-chronic studies through a variety of mechanisms (Khathi et al, 2013;Mkhwanazi et al, 2014;Musabayane et al, 2010;Ngubane et al, 2011). Furthermore, these triterpenes have previously been reported to reduce food intake through unknown mechanisms (Khathi et al, 2013;Mkhwanazi et al, 2014).…”
Section: Introductionmentioning
confidence: 92%
“…Experimental type 1 diabetes mellitus was induced in male Sprague-Dawley rats using a previously described protocol (Mapanga et al, 2009;Ngubane et al, 2011). Briefly, each animal was administered a single intraperitoneal injection of 60 mg/kg streptozotocin in freshly prepared 0.1M citrate buffer (pH 6.3).…”
Section: Induction Of Diabetesmentioning
confidence: 99%